DEVELOPMENT OF ASSESSMENT INSTRUMENTS BASED ON HIGHER ORDER THINKING SKILLS (HOTS) FOR ELEMENTARY SCHOOL STUDENTS - Suratmi Suratmi; Laihat Laihat; Asnimar Asnimar (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2020)
AbstractThis study aims to produce an assessment instrument based on Higher-Order Thinking Skills for elementary school students. The assessment instrument was made in the form of a cognitive ability test for elementary school students of the sixth grade in Science subject at Elementary School. This research used research and development methods. The research design used is the Borg and Gall development model. The stages of development research include 1) Research and Information Gathering, 2) Planning, 3) Initial Product Development, 4) Initial Field Testing, 5) Main Product Revision, 6) Main Field Testing, 7) Operational Products Revision. The instruments used were interviews, product quality assessment sheets and questionnaires. The results of this research are a collection of valid, practical, and reliable HOTS-based assessment instruments. From the expert review results obtained an average assessment results percentage from the experts’ validation of 93.57 with the category of very feasible. HOTS-based assessment instruments can be used in learning in the elementary schools.Keywords: Assessment, HOTS, Elementary School